Water Supply Potential for Agropolitan Concept - Ernanda, Heru; Andriyani, Idah (The University of Lampung, 2022)
One of the obstacles to the development of Tongas District - Probolinggo Regency as an agropolitan area is the Limited of availability of water in Tongas Village. Kelampok village only has technical fields area of 105 hectares (14.45%) and the rest are rain-fed. The goverment of Probolinggo regency plans to develop Kelampok Reservoir. This study aims to research the potential of land and water for development of Kelampok Reservoir as a Water source for agriculture. To develop the Kelampok Reservoir engineering model, required main discharge, the location of the reservoir plan, and flood discharge. The results of the main discharge calculation using tank model had a maximum discharge of 332 L/s in The first decade do March and The discharge si only available for November to May. Hydrologically and geologically, the study area has an average rainfall of 1,430 mm/y with the type of Oldeman Climate classification is D4 and dominated by regosol soil types (96.60%). Kelampok Reservoir is engineered with (i) the full capacity of catchment is 7.103 m3 and the effective capacity is 6,877 m³, (ii) the reservoir has a total width of 10.00 m and an effective width is 9.20 m, and (iii) planned to operate from early July to September (10 decades/10 days) with an discharge output of 789 L/d or 0.913 L/s. Key words: Agropolitan, Discharge, Irrigation, Natural Resource, Reservoir